8428 Rare Variants in the MECP2 Gene in Two Boys with Central Precocious Puberty - Ana Pinheiro Machado Canton; Jacobo Buelvas Mebarak; Melissa Magnuson; Stephanie Roberts; Nelly Mauras; Matthew D. Benson; Selma F. Witchel; Rona S. Carroll; Ana Cláudia Latronico; Ursula B. Kaiser; Ana Paula Abreu (2024)
Abstract Disclosure: A.P. Canton: None. J.B. Mebarak: None. M. Magnuson: None. S. Roberts: None. N. Mauras: None. M. Benson: None. S. Witchel: None. R.S. Carroll: None. A. Latronico: None. U.B. Kaiser: None. A. Abreu: None. Introduction: Central precocious puberty (CPP) occurs more frequently in girls and is usually labelled as idiopathic; however, in boys organic causes are more frequent. Identification of imprinted genes causing CPP have revealed epigenetic mechanisms underlying puberty. MECP2, an X-linked gene, encodes a methylated DNA reader protein with a role in gene transcription. MECP2 loss-of-function mutations usually cause Rett syndrome, a severe neurodevelopmental disorder that may be associated with early pubertal development. Recently, rare variants in MECP2 have been recognized in girls with sporadic CPP with or without mild neurodevelopmental disorders. In our cohort of 78 patients with idiopathic CPP, no MECP2 mutations were identified in 73 girls. In this study, five boys with CPP were evaluated for potential MECP2 sequence variants. Methods and Results: Five boys with CPP were screened for MECP2 sequence variants using Sanger sequencing. At the time of CPP diagnosis, they had median (interquartile range) chronological age 9.2 yr (4.3), bone age advancement 2.1 yr (3.5), height SDS 2.3 (1.5), basal LH levels 1.6 IU/L (0.9), and testosterone levels 370 ng/dL (570). Organic causes of CPP were excluded. No MKRN3 or DLK1 mutations were identified. Familial segregation analysis was performed when appropriate. We identified a hemizygous MECP2 variant in a boy (Patient 1) who presented at age 2.7 yr with sporadic CPP. In addition, he had speech delay and behavioral changes, defined as autism spectrum disorder by neuropsychological assessment. He harbored an extremely rare (gnomAD AF=0.000004956) missense variant (p.Val312Ile) in exon 3 of MECP2, encoding the transcriptional repression domain, critical for protein function. The p.Val312Ile mutation was classified as likely pathogenic (ACMG criteria) with a potential association with the phenotype. Another hemizygous MECP2 variant was identified in a boy (Patient 2) who presented at age 8.0 yr with sporadic CPP; he had no neurodevelopmental conditions. He harbored a rare (gnomAD AF=0.00008) missense variant (p.Arg366Cys) in exon 3, encoding the C-terminal domain, classified as a variant of uncertain significance (ACMG criteria). Familial segregation analysis revealed that both boys inherited the MECP2 variants from their unaffected mothers, consistent with a pattern of clinical variability described in women with defects in X-linked genes.Conclusions: We identified rare MECP2 variants in two boys with sporadic CPP without classic features of Rett syndrome, expanding the phenotype of patients with MECP2 mutations, as described in girls. The MECP2 p.Val312Ile variant was likely pathogenic, whereas the functional significance of the p.Arg366Cys variant in still indeterminate. These findings provide additional evidence for a role of MECP2, an epigenetic factor, in the hypothalamic control of pubertal timing. Presentation: 6/1/2024